Motivational Personality Sphere and Psychoemotional Features in Patients with Drug Addiction Disorders atDifferent Stages of the Treatment and Rehabilitation Process (Part 2) - E.V. Fadeeva; A.M. Lanovaya (Психология и право)
The aim of the study was to analyze dynamic changes in the motivational sphere of personality and psychoemotional features of patients with drug addiction disorders at different stages of the treatment and rehabilitation process. The study involved 226 patients: 163 men (72.1%) and 63 women (27.9%) with narcological disorders. The following scales were used: the scale of stages of readiness for change and aspiration to treatment (Socrates), the scale of depression, anxiety and stress (DASS-21) and the scale of general self-efficacy (GSE). During the stabilising phase of therapy: 1) women showed significantly higher scores on the Socrates scale total score (p≤0.001), the Ambivalence subscale (p≤0.001) and the Action subscale (p≤0.05); 2) inverse correlations were found between the result on the Action subscale (Socrates) and signs of depression (r=-0.350, p≤0.05), anxiety (r=-0.452, p≤0.01) and stress (r=-0410, p≤0.01) (DASS-21). The results of the psychoemotional state revealed that patients with signs of stress were significantly more likely to undergo medical rehabilitation treatment and less likely to be discharged early, which allows the results to be used in targeted medical rehabilitation programmes.